Subjectivity analysis using machine learning algorithm - Ahmed, Erfan; Azad, Muhitun; Islam, Md. Tanzim; Sazzad, Md. Asad Uzzaman (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2016.